2022
DOI: 10.1002/stco.202200028
|View full text |Cite
|
Sign up to set email alerts
|

Buckling resistance of longitudinally stiffened panels with closed stiffeners under direct longitudinal stresses

Abstract: The buckling behaviour of panels may be determined according to EN 1993-1-5 [1]. Most of the design rules relating to stiffened panels in EN 1993-1-5 were derived on the basis of opensection stiffeners. Several recent investigations have shown that the application of the design rules according to EN 1993-1-5 considering the torsional stiffness of the stiffeners may overestimate the resistance of the panels. Therefore, the recent Amendment A2 to EN 1993-1-5 states that the torsional stiffness of stiffeners shou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…If we assume a buckling shape with one half-wave in the transverse direction (n = 1), the buckling coefficient kσ,p is a function of m, α and the nondimensional parameters δ, γ and θ of the stiffener. Finally, by minimizing the function (11), kσ,p can be defined in two branches, the first part corresponding to the value of kσ,p for m = 1 and the second part representing the minimum value of the function:…”
Section: Considering Torsional Rigidity Of Closed Longitudinal Stiffe...mentioning
confidence: 99%
See 3 more Smart Citations
“…If we assume a buckling shape with one half-wave in the transverse direction (n = 1), the buckling coefficient kσ,p is a function of m, α and the nondimensional parameters δ, γ and θ of the stiffener. Finally, by minimizing the function (11), kσ,p can be defined in two branches, the first part corresponding to the value of kσ,p for m = 1 and the second part representing the minimum value of the function:…”
Section: Considering Torsional Rigidity Of Closed Longitudinal Stiffe...mentioning
confidence: 99%
“…If the deformation was greater than 0.5, the buckling mode was defined as the global buckling mode. More information on the methodology of the global buckling identification can be found in [11]. [6,11] 4…”
Section: Considering Torsional Rigidity Of Closed Longitudinal Stiffe...mentioning
confidence: 99%
See 2 more Smart Citations
“…New investigations [4], [5] concluded that the torsional stiffness of closed longitudinal stiffeners should be neglected in the calculation of critical buckling stresses to achieve safe results. Pourostad [6] proposes a new interpolation formula for the EN 1993-1-5 buckling design to consider the torsional stiffness of stiffeners, see Equations ( 2) and (3). The proposal in [6] is derived based on longitudinally stiffened panels under direct longitudinal stresses.…”
Section: Introductionmentioning
confidence: 99%